A Meta-analysis of Sanyrene in preventing radiation dermatitis of head and neck tumor (赛肤润预防头颈部肿瘤放射性皮炎的Meta分析) - ZHENG Ya (郑雅); ZENG Guqing (曾谷清); PENG Lingying (彭玲英); NI Xiaoyan (倪晓燕); WANG Aoyi (王傲一); PAN Rongjia (潘荣佳); NIAN Fang (年芳) (Association of Integrative Nursing, 2021)
Objective To systematically evaluate the efficacy of Sanyrene in preventing radiation dermatitis after radiotherapy for head and neck tumors. Methods The data of PubMed, Cochrane Library, Embase, Web of Science, CBM database, Viper database, Wanfang database and CNKI database were searched, and randomized controlled studies on the use of Sanyrene to prevent radiation dermatitis were collected. The intervention group used Sanyrene, and the control group used other preventive medications or placebos or conventional methods (such as flushing with water). The search time limit is from the establishment of the database to December 31, 2019. Two independent reviewers screened, evaluated and extracted the literature, and Meta-analysis was performed by RevMan 5. 3 software. Results A total of 10 articles that met the criteria were included, including 842 patients with head and neck tumor. Meta analysis results showed that the total incidence of radioactive dermatitis in the intervention group was statistically significant compared with the control group ［OR=0. 24, 95%CI(0. 15, 0. 37), P<0. 05］. The incidence of grade Ⅰradiation dermatitis in the intervention group was significantly different from that in the control group ［OR=2. 70, 95%CI(1. 92, 3. 81), P<0. 05］. The incidence of grade Ⅱradiation dermatitis or above in the intervention group was significantly different from that in the control group ［OR=0. 19, 95%CI(0. 13, 0. 27), P<0. 05］. Conclusion Sanyrene can effectively reduce the incidence of radioactive dermatitis in head and neck tumors, alleviate the severity of radioactive dermatitis, and reduce the incidence of radioactive dermatitis of grade Ⅱand above. (目的 系统评价赛肤润在预防头颈部肿瘤放射治疗后放射性皮炎中的应用效果。方法 计算机检索PubMed、Cochrane Library、Embase、Web of Science、CBM数据库、维普数据库、万方数据库和CNKI数据库, 收集运用赛肤润预防放射性皮炎的随机对照研究, 对照组使用其他预防用药或安慰剂或常规方式干预组使用赛肤润, 检索时限为各数据库建库至2019年12月31日。由2名独立的评价者对文献进行筛选、质量评价和数据提取后, 采用 RevMan 5. 3 软件进行meta分析。结果 共纳入符合标准的文献10篇, 共计842例头颈部肿瘤患者。Meta分析结果显示: 干预组放射性皮炎总发生率与对照组比较, 差异有统计学意义［OR=0. 24, 95%CI(0. 15, 0. 37), P<0. 05］; 干预组Ⅰ级放射性皮炎发生率与对照组比较, 差异有统计学意义［OR=2. 70, 95%CI(1. 92, 3. 81), P<0. 05］; 干预组Ⅱ级及以上放射性皮炎发生率与对照组比较, 差异有统计学意义［OR=0. 19, 95%CI(0. 13, 0. 27), P<0. 05］。结论 赛肤润能有效降低头颈部肿瘤放射性皮炎的发生率、减轻放射性皮炎的严重程度, 降低Ⅱ级及以上放射性皮炎的发生率。)